Fine root morphological characteristics and biomass distribution characteristics of different artificial forests in coastal salt land and their influencing factors - Wang, Zhibao; Liang, Jing; Jiang, Hong; Gao, Xiangbin; Yu, Shouchao; Zhou, Chuanjie; Guo, Yuwei (Frontiers in Plant Science, 2025)
To elucidate the ecological adaptations of fine root morphological traits and biomass in tree species with different life forms to coastal saline soil, five species (Robinia pseudoacacia(RP), Sapium sebiferum(SA), Salix matsudana(SM), Quercus virginiana(QV), Ligustrum lucidum(LI)) were investigated using continuous root coring. Fine root morphological traits, biomass distribution, and their relationships with soil water, temperature, electrical conductivity, pH, total nitrogen, total phosphorus, and soil organic matter were analyzed to reveal species-specific adaptation strategies. Results showed significant differences (P<0.05) in fine root morphological indices (specific root length, specific root surface area, root length density, and root surface area density). RP exhibited the highest specific root length (135.38 m·g-1) and specific root surface area (1141.07 cm²·g-1), while QV showed the lowest values (39.17 m·g-1 and 315.22 cm²·g-1, respectively). Both root length density and root surface area density decreased with increasing soil depth. Fine root biomass differed significantly among species (P<0.01), with LI having the highest biomass (273.42 g·m-2) and RP the lowest (77.05 g·m-2). Vertically, biomass declined with depth; horizontally, it decreased with distance from the trunk. Root extinction coefficients indicated QV and RP as deep-rooted species, while LI, SM and SA were shallow-rooted. Seasonal dynamics revealed unimodal patterns in live and dead fine root biomass for RP, LI, QV, and SA. In contrast, SM exhibited a unimodal pattern in live fine root biomass but a distinct bimodal pattern in dead fine root biomass. Correlation analysis identified soil electrical conductivity, soil water, and total nitrogen as primary environmental drivers of fine root traits and biomass.